Re-writing the russian conquest of Central Asia - Morrison, Alexander Stephen (Nazarbayev University, 2014)
Between 1845 and 1895 roughly 1,500,000 square miles of territory in Central Asia were added to the Russian empire. Russia's expansion southwards across the Kazakh steppe into the riverine oases of Turkestan was one of the nineteenth century's most dramatic examples of imperial conquest, but remains under-researched and misinterpreted. This is partly because for many years Russia was not considered to be a "colonial" empire at all, as both western and Soviet historians claimed that the cultural and racial hierarchies of western colonialism were absent from the Tsar's domains. It is also because much of the material needed to study it was unavailable to western scholars.
Keywords: Central Asia; colonial; Soviet historians; conquest